PENGARUH MOTIVASI, DISIPLIN, KINERJA DAN KEPUASAN KERJA PEGAWAI TERHADAP PENGENDALIAN INTERNAL PADA KANTOR KEPALA DESA PEMATANG SELENG, KABUPATEN LABUHANBATU - Nandasari, Susi Tri (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of motivation, discipline, performance and job satisfaction at the Head Office of Pematang Seleng Village, Labuhanbatu Regency. This type of research is associative research. Data collection in this study was carried out through a survey approach with quantitative descriptive research type by distributing questionnaires to 35 respondents, while the population used in this study were employees of the village head office. Data collection techniques were carried out by interviews, questionnaires and documentation study. The data analysis tool used in this study used SPSS (Statistical Product Software Solution). The data analysis techniques in this study were descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (test), simultaneous significant testing (F test). , and testing the coefficient of determination (R2). The results showed that simultaneously the motivation variable has a significant effect on internal control F count 6,910> F table 2.69 with a significant value of 0.000 <0.05, partially motivation has an effect, although not too significant on control Internal obtained the value of t count-1.077 <t table 1.697 and the probability value of t that is 0.290> 0.05, partially discipline has an effect, although not too significant on internal control, the value of tcount is -0.117 <ttable 1.697 and the probability value of t is 0.911> 0.05. , performance has an effect, although not very significant for internal control, the value obtained is 1.790> t table 1.697 and the probability value t is 0.084> 0.05. Job satisfaction has a significant effect on internal control, the t value is 3.516> t table 1.697 and the probability value t is 0.001 <0.05.).